(untitled) (Scientific journal of the Fergana State University, 2024)
This article lists the emblems depicting Isajan Sultan in the stories of Shamal. As you know, landscape is the main component that plays an important role in highlighting the content of a work of art, in the system of events, and in the plot structure. This article shows how the wind penetrates the work as part of the landscape and performs various tasks in accordance with the author’s purpose. By the nature of the wind’s identity with space and time, it can be said that it comes from the infinite artistic possibilities of the Creator. In particular, the images of the wind in love, strength, fate, relationships of people in society, reflection of spiritual passions, conflicts in the image of the wind, storms are analyzed in detail on the example of Adib’s stories “windy night”, “Aidinbulak”, “Sofia”, “army of talismans”.